1963
DOI: 10.1103/physrev.130.852
|View full text |Cite
|
Sign up to set email alerts
|

Precision Measurement of thegFactor of the Free Electron

Abstract: The measurement reported is essentially a refinement of an earlier measurement in which the g factor was found to ±2.4 parts in 10 6 . The method is as follows: 100-keV electrons in 0.2-/*sec bunches move parallel to a magnetic field and strike a gold foil. The part of an electron bunch which is scattered at right angles, and which, consequently, is partially polarized, is trapped in the magnetic field and held for a measured length of time (up to 1.9 msec). The bunch is then released from the trap and allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

1966
1966
2003
2003

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…After that the situation has changed. BMT equation successfully confirmed the results of experiments on precision determination of the anomalous magnetic moment of an electron [13,14], muon [15] and also the masses of a number of heavy elementary particles [16]. As it turned out well to explain the experimentally observed effect of radiative self-polarization of electrons [17,18] within the frameworks of the quasiclassical spin theory as well as the Dirac quantum theory.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…After that the situation has changed. BMT equation successfully confirmed the results of experiments on precision determination of the anomalous magnetic moment of an electron [13,14], muon [15] and also the masses of a number of heavy elementary particles [16]. As it turned out well to explain the experimentally observed effect of radiative self-polarization of electrons [17,18] within the frameworks of the quasiclassical spin theory as well as the Dirac quantum theory.…”
Section: Introductionsupporting
confidence: 69%
“…Π αβ Π αβ = const is well known spin invariant. We emphasize that equation (14) was derived under assumption that the Frenkel condition (1) is valid.…”
Section: Formalism Of Angular Momentum Tensormentioning
confidence: 99%
“…5 At the time of the observation of the CP violation in 1964, an upper limit to the EDM of the neutron 6 186 39 of /JLJV/£<5X1(T 20 cm had been reported. The best upper limit for the electron 7 was on the order of 4xl0~1 6 cm. Significant improvements on the electron-moment upper limits have come about for two reasons: (i) the development of highly sensitive methods of measuring small shifts due to an electric field in atomic rf resonances, 8 and (ii) a theoretical interpretation by Sandars 9 ' 10 who showed that electric field (Stark shift) measurements on neutral atoms could lead to information on the EDM of the electron.…”
Section: Introductionmentioning
confidence: 98%
“…3,7 Partially polarized electrons obtained by Mott scattering are confined in a weak magnetic mirror trap (mirror ratio 1.0001:1) for an accurately measured time T. They are then ejected from the trap and undergo a second Mott scattering. Those which scatter through 90° are counted.…”
mentioning
confidence: 99%
“…3. At the desired ejection time, a positive pulse applied to the eject cylinder gives half the trapped electrons sufficient energy to reach the analyzing foil.…”
mentioning
confidence: 99%